Algorithms for the Bregman k-Median Problem - Ackermann, Marcel Rudolf

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Coresets and Approximate Clustering for Bregman Divergences - Ackermann, Marcel R.; Blömer, Johannes (Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms)

Three-Valued Spotlight Abstractions - Schrieb, Jonas; Wehrheim, Heike; Wonisch, Daniel (FM 2009: Formal Methods)

Linkages between Financial Deepening, Trade Openness and Economic Development: Causality Evidence from Sub-Saharan Africa - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (World Development)

The Optimal Distance to Port for Exporting Firms - Gries, Thomas; Naudé, Wim (Journal of Regional Science)

Explaining Regional Export Performance in a Developing Country: The Role of Geography and Relative Factor Endowments - Gries, Thomas; Naudé, Wim (Regional Studies)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (Advances in Cryptology - ASIACRYPT 2009, 15th International Conference on the Theory and Application of Cryptology and Information Security, Tokyo, Japan, December 6-10, 2009. Proceedings)

Modifications in Dietary Fat Quality Are Associated with Changes in Serum Lipids of Older Adults Independently of Lipid Medication - Buyken, Anette; Flood, Victoria; Rochtchina, Elena; Nestel, Paul; Brand-Miller, Jennie; Mitchell, Paul (The Journal of Nutrition)

Immigrational Background Affects the Effectiveness of a School-based Overweight Prevention Program Promoting Water Consumption - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Toschke, André M.; Reinehr, Thomas; Kersting, Mathilde (Obesity)

Relative validity of a self-completion 24 h recall questionnaire to assess beverage consumption among schoolchildren aged 7 to 9 years - Muckelbauer, Rebecca; Libuda, Lars; Kersting, Mathilde (Public Health Nutrition)
Abstract Objective Drinking habits in children are associated with diet quality, but validated assessment tools for large-scale studies in young children are lacking. Therefore, we validated a self-completion 24 h recall questionnaire (RQ) focusing on beverage consumption with a 24 h weighed record (WR). Design Thirty-five voluntary participants from the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study cohort aged 7–9 years completed the RQ. The illustrated RQ required ticking the number of glasses of seven beverage categories consumed in five time intervals in the previous 24 h. As a reference, parents completed weighed records of their child’s diet. Agreement between the RQ and WR was tested by classification into consumers and non-consumers (kappa coefficients, κ ), by the children’s ability to estimate the exact beverage and total volume consumed (Wilcoxon signed-rank test, Spearman rank correlation), and by ranking children according to reported beverage volumes. Results The RQ and WR showed a good level of agreement for classifying participants into consumers and non-consumers of the single beverage categories ( κ values between 0·78 and 0·94). Correlation coefficients for the volume of the single categories ranged between 0·81 and 0·91. The total beverage volume was overestimated in the RQ, on average, by 114 ml ( P = 0·015). Agreement in ranking into tertiles by beverage volume was moderate to good for juice/soft drinks ( κ = 0·44), milk ( κ = 0·57) and water ( κ = 0·70), but fair for the total beverage volume ( κ = 0·23). Conclusions Our self-completion 24 h RQ could estimate the consumption of several beverage categories among young children at the group level, but quantification of total beverage volume was flawed.

Relation of Dietary Glycemic Index, Glycemic Load, and Fiber and Whole-Grain Intakes During Puberty to the Concurrent Development of Percent Body Fat and Body Mass Index - Cheng, G.; Karaolis-Danckert, N.; Libuda, Lars; Bolzenius, K.; Remer, T.; Buyken, Anette E. (American Journal of Epidemiology)

Long-term process evaluation of a school-based programme for overweight prevention - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Child: Care, Health and Development)

A Simple Dietary Intervention in the School Setting Decreased Incidence of Overweight in Children - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Reinehr, Thomas; Kersting, Mathilde (Obesity Facts)

Promotion and Provision of Drinking Water in Schools for Overweight Prevention: Randomized, Controlled Cluster Trial - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Toschke, A. M.; Reinehr, T.; Kersting, M. (PEDIATRICS)

Erfolgreich Computer und Internet in Grundschulen integrieren – eine empirische Analyse aus Sicht der Schulentwicklungsforschung - Eickelmann, Birgit; Schulz-Zander, Renate; Gerick, Julia (Europäisierung der Bildung - Konsequenzen und Herausforderungen für die Grundschulpädagogik)

The Dagstuhl Core - Dumitrescu, Theodor; Kepper, Johannes; Kornstädt, Andreas; Röwenstrunk, Daniel; Roland, Perry; Sapp, Craig; Selfridge-Field, Eleanor; Wiering, Frans; Wiggins, Geraint A.

Soft drinks and body weight development in childhood: is there a relationship? - Libuda, Lars; Kersting, Mathilde (Current Opinion in Clinical Nutrition and Metabolic Care)

Getränkeverzehr und Übergewicht bei Kindern - Libuda, Lars; Muckelbauer, R.; Kersting, M. (Journal für Ernährungsmedizin)

Einfluss des Konsums von Erfrischungsgetränken auf den Ernährungs- und Gesundheits¬status von Kindern - Libuda, Lars (Ernährungsumschau)